Literasi Keuangan: Pelatihan Investasi Saham Melalui Pengenalan Pasar Modal Indonesia kepada Investor Milenial - Utomo, Langgeng Prayitno; Hartanti, Benih (Journal of Dedicators Community, 2021)
Understanding of finance is important, especially for people who want to invest, it is aimed at obtaining maximum returns or returns from investments. The condition of the selected service partners, namely students and the general public who have an interest in investing, currently do not really understand personal finance so they are unable to manage their own finances which results in not understanding how to start investing. The purpose of this activity is to introduce the importance of understanding personal finance so as to be able to measure the extent to which personal financial conditions can be used to invest in the Indonesian capital market to service partners, namely young potential investors. The training activities are carried out in the computer laboratory of STIE PGRI Dewantara Jombang with lecture, question and answer methods, and practice. The material for the activity consists of the basic theory of financial management, introduction to investment, fundamental and technical analysis, and trading simulations. The results of this activity are: 1) service partners have a new understanding of financial literacy and personal finance well; 2) partners are better prepared when they are going to invest in shares or trade in the capital market; 3) the interest of partners to be able to invest is higher than before.